Novas tecnologias no armazenamento de peras europeias: impacto de atmosfera controlada dinâmica e temperatura no amadurecimento - Wendt, Lucas Mallmann (2024)
Pears (Pyrus communis L.) is a seasonal and climacteric fruit, which requires the use of appropriate post-harvest conditions to extend the supply period. Therefore, pears are stored mainly in controlled atmospheres (CA), however, the development of internal disorders, reduction in the production of volatile organic compounds (VOCs) and loss of ripening capacity are associated with storage in CA. Dynamic controlled atmosphere storage (DCA) which uses extremely low oxygen partial pressure (pO2) and is being used worldwide to maintain quality and extend the storage period. Furthermore, temperature affects fruit quality, as it influences the speed of chemical and biochemical reactions. Therefore, in this work experiments were developed, which are described in 3 chapters, with the objective: [1] evaluate the effect of storage in DCA monitored by respiratory quotient (DCA-RQ) and to establish the optimal RQ, considering its impact on the physicochemical quality and production of VOCs for ‘Santa Maria’ and ‘Rocha’ pears; [2] evaluate the response of ‘Santa Maria,’ ‘Rocha,’ and ‘Packham’s’ pears stored close to the lower oxygen limit by using DCA techniques, monitored by RQ and carbon dioxide production (CD), comparing them with conventional CA and extremely low oxygen (ELO) in relation to the impact on the quality and production of VOCs; and [3] evaluate the possibility of storing ‘Rocha’ pear at a higher temperature (0.5 °C) and [4] evaluate the effectiveness of storage in DCA-ARP (anaerobic respiration point) in comparison to CA, ELO and DCA-RQ 1.2 in physicochemical quality and synthesis of VOCs after 6 months plus 1 and 9 days at 20 °C. It was observed that ‘Santa Maria’ and ‘Packham's’ pears stored under CA, had a more yellow skin coloration and less flesh firmness, resulting from higher ethylene production and respiration rate, while in the Rocha cultivar, stored under CA, the fruit presented greater flesh firmness and lower ethylene production after 7 days at 20 °C. Storage of ‘Rocha’ pears under DCA-CD and DCA-RQ independently of the RQ level suppressed the production of ethyl acetate, butyl acetate, hexyl acetate, methyl acetate, pentyl acetate and propyl acetate. However, storage in different modalities DCA resulted in a higher concentrations of ethyl acetate and butyl acetate in ‘Santa Maria’ pears and in Packham's cultivar resulted in a higher concentrations of ethyl acetate and lower concentrations of hexyl acetate and methyl acetate. ‘Rocha’ pears, regardless of the temperature and storage conditions, developed a yellower fruit skin color and buttery and juicy texture after 9 days at 20 °C. Furthermore, storage under CA and ELO at -0.5 °C results in a lower incidence of decay and a higher percentage of healthy fruit after 1 and 9 days at 20 °C. However, at temperature of 0.5 °C under CA, there was a greater emission of linear ester. In conclusion, taking into account the physicochemical quality and synthesis of volatile compounds, the storage of pears in conditions with extremely low pO2 (ELO and ACD) at a temperature of -0.5 °C is not recommended, whereas in the Rocha cultivar, it is possible to use extremely low pO2, especially in ACD-PRA at a storage temperature of 0.5 °C.